STUDI KEANEKARAGAMAN PTERIDOPHYTA TERESTRIAL DI KAWASAN HUTAN WISATA AIR TERJUN JUMOG DESA BERJO NGARGOYOSO KARANGANYAR PROVINSI JAWA TENGAH - NUR FITRIANTI, RIZKA, Efri Roziaty, S. Si., M. Si sel (2016)
The research on ecological studies of terrestrial Pteridophytes in the forest area waterfalls Jumog Berjo Village Ngargoyoso Karanganyar Central Java was conducted on February until March 2016. The aimed of this research was determining the level of diversity terrestrial pteridophytes in the area waterfalls. This research was using purposive sampling to determine the location of plots. The research plots consisted of 15 plots. Result of the study found 15 species from the genus Selaginella (Selaginella ornata), 1 species of the genus Cyathea (Cyathea contaminans) and 13 species of the genus Polypodiaceae consist of Adiantum raddianum, A.capillus-veneris, A.hispidulum, Deparia petersenii, Chingia ferox, Diplazium sp., D. procumbens, Nephrolepis biserrata, Tectaria melanocaula, T. fuscipes, Pteris biurita and pteridophyta species A and B. The dominant percentage of plant seen from calculation highest INP is a further Adiantum raddianum then Deparia petersenii while the lowest is INP in plant Diplazium sp. The index of diversity (H') is 0,821. This index indicating that low pteridophytes diversity in tourist area Jumog waterfall. The higest diversity was found Selaginella ornata is 0,150 while the lowest was of plant is Cyathea contaminans and Diplazium sp.